Insulin-like growth factor-1 decreases apoptopic cell death, but not proapoptopic protein expression in a transient forebrain ischemia-reperfusion model in the rat - (:unkn) unknown (My University, 2001)
Objective: Cerebral ischemia results in both necrotic and apoptotic cell death. It has been suggested that approaches directed at disrupting the apoptotic process and expression of proapoptotic proteins might be beneficial for preserving functional neuronal tissue after an ischemic insult. The aim was to evaluate the presence of apoptotic cell death and the pattern of expression of proapoptotic protein (bax) in a transient forebrain cerebral ischemia model and to observe the potential benefits of a neurotrophic factor IGF-I on these parameters. Methods: Female/male Wistar rats weighing 200-240g were subjected to transient forebrain ischemia by bilateral carotid artery occlusion combined with systemic hypotension for 10 minutes. Three reperfusion periods were performed as 1h, 24h and 7 days. The experiment was then conducted in two arms: in group I (n=6 for each reperfusion group), intracisternal injection of vehicle or 10 μg/rat of IGF-I was performed at all reperfusion periods, and these rats were evaluated for the presence of apoptosis and bax protein expression. Group II (n=4 for each reperfusion group) was evaluated for protein oxidation at the three reperfusion periods. Results: Apoptosis was significantly higher (p<0.01) in the vehicle group compared to the sham group, and IGF-I treatment resulted in a significant decrease of apoptosis compared to the vehicle treated group at 24 hour reperfusion. Moreover, a peak in apoptotic cell death at 24 hour reperfusion was observed, however remaining just short of significance (p = 0.0730). No difference in bax protein expression and protein oxidation could be demonstrated between reperfusion periods and after IGF-I use. Conclusion: 10μg/rat of IGF-I produces a significant suppression in apoptotic cell death at 24 hours reperfusion following transient forebrain ischemia.
Keywords: Apoptosis; Forebrain ischemia; IGF-I; Rat